2000
DOI: 10.1677/joe.0.1670305
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen modulates osteoblast proliferation and function regulated by parathyroid hormone in osteoblastic SaOS-2 cells: role of insulin-like growth factor (IGF)-I and IGF-binding protein-5

Abstract: Although there is clinical evidence showing that combined therapy with parathyroid hormone (PTH) and estrogen is additively effective in increasing the bone mass of patients with osteoporosis, the mechanism of the interaction between these hormones remains unclear. The present study was performed to determine whether estrogen would affect osteoblast proliferation and function modulated by PTH in human osteoblastic SaOS-2 cells. Human PTH-(1-34) significantly inhibited [3 H]thymidine (TdR) incorporation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…However, male mice in the absence of PTH tended to have more osteoprogenitor cells and higher ALP activities than female mice, and this difference persisted following PTH administration. In a previous study, Nasu et al(2000) demonstrated that PTH stimulated osteoblast function such as ALP activity and collagen synthesis following pretreatment with estrogen, but it did not affect osteoblast function in the absence of estrogen P<0·05 control vs PTH treatment; F, female; M, Male; TV, total bone volume (mm pretreatment, suggesting that estrogen plays an important role in the anabolic effects of PTH on osteoblast differentiation. This suggests that the gender difference in the anabolic effects of PTH on BMSC is at least partly based on estrogen action.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, male mice in the absence of PTH tended to have more osteoprogenitor cells and higher ALP activities than female mice, and this difference persisted following PTH administration. In a previous study, Nasu et al(2000) demonstrated that PTH stimulated osteoblast function such as ALP activity and collagen synthesis following pretreatment with estrogen, but it did not affect osteoblast function in the absence of estrogen P<0·05 control vs PTH treatment; F, female; M, Male; TV, total bone volume (mm pretreatment, suggesting that estrogen plays an important role in the anabolic effects of PTH on osteoblast differentiation. This suggests that the gender difference in the anabolic effects of PTH on BMSC is at least partly based on estrogen action.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, we found that PTH increased the mRNA levels of IGF-I and its receptor (IGF-IR) only in male mice. Although several reports suggested a stimulatory effect by estrogen on IGF-I synthesis by osteoblasts (Watson et al 1995, Nasu et al 2000, recent findings indicate that the influence of estrogen on IGF-I gene expression is complex and perhaps indirect (McCarthy et al 1997). Estrogen is able to diminish IGF-I gene activation by PTH or PGE2 as well as by GH (McCarthy & Centrella 2001).…”
Section: Discussionmentioning
confidence: 98%
“…Part of these differences is most likely due to the sex steroid environment [15, 16, 17]. In addition, the higher expression of IGFBP-5 in females during pubertal development may be directly related to their higher levels of estrogens, since in some tissues IGFBP-5 expression is stimulated by estradiol [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Earlier it was thought that estrogen prevented osteoporosis exclusively by inhibiting bone resorption. Later studies revealed that estrogen stimulated cell proliferation in a dose dependent manner and increased the steady state levels of mRNA encoding a1 chain of type I collagen [Ernst et al, 1988;Nasu et al, 2000]. In vivo administration of estradiol to rats also could enhance the proaI collagen gene expression in the uterus [Komm et al, 1987].…”
Section: Estrogen As a Regulator Of Collagen Synthesismentioning
confidence: 99%